Kalmyks in the Persian Campaign of 1722: Introducing Some Newly Discovered Documents - Vladimir T. Tepkeev; Narma A. Kamandzhaev (Oriental Studies)
Introduction. Recent times witness an increased interest in the written heritage of the seventeenth- and eighteenth-century Russian-Kalmyk interactions. So, the paper introduces some collections from a variety of previously unpublished orders and edicts of Peter I and Khan Ayuka from the period of (including preceding arrangements) the 1722 Persian Campaign. Goals. The work seeks to present a number of newly discovered document narratives pertaining to Russian-Kalmyk relations in Peter the Great’s era. Materials. The article focuses on collections of the Russian State Archive of Ancient Acts and Archive of Foreign Policy of the Russian Empire that contain unique correspondence materials between the Kalmyk ruler and the Russian emperor. Results. Publications of such documents shall essentially contribute to the study of the seventeenth- and eighteenth-century Russian-Kalmyk contacts. The text mentions most interesting details of how Kalmyk cavalry units would prepare and participate in the Persian Campaign of 1722. Conclusions. Essentials of Peter the Great’s orders and edicts — as well as those of Khan Ayuka — attest to the Russian government was perfectly aware of the actual situation along its southern borders. The edict’s text shows the government did pay particular attention to military training of irregular troops, and sought to secure the latter receive comprehensive support and stipulated combat pays.